2018
DOI: 10.1021/acs.chemrev.7b00322
|View full text |Cite
|
Sign up to set email alerts
|

Forty Years after “Heterodiene Syntheses with α,β-Unsaturated Carbonyl Compounds”: Enantioselective Syntheses of 3,4-Dihydropyran Derivatives

Abstract: This review is focused on the enantioselective synthesis of 3,4-dihydropyran derivatives, whose importance as chiral building blocks in the synthesis of bioactive molecules and natural products is well established. The review analyzes the different synthetic strategies by grouping them as a function of the atom numbers of the reagents involved. Starting from the classical [4 + 2] and [2 + 4] approaches, the [3 + 3], [5 + 1], and [6] strategies have been sequentially analyzed, and for each of them, the asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 483 publications
(1,101 reference statements)
0
58
0
Order By: Relevance
“…Chromane [4] arenes were obtained by the Diels-Alder reaction between the o-quinone methides of resorcin [4] arene and styrenes [34]. The authors identified their compounds as chiral, but actually, they were racemic mixtures.…”
Section: Cycloaddition Of Ortho-quinone Methidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromane [4] arenes were obtained by the Diels-Alder reaction between the o-quinone methides of resorcin [4] arene and styrenes [34]. The authors identified their compounds as chiral, but actually, they were racemic mixtures.…”
Section: Cycloaddition Of Ortho-quinone Methidesmentioning
confidence: 99%
“…Great work in summarizing the asymmetric synthesis of these compounds has been carried out [3][4][5][6]. However, in the last three years, many other new synthetic methods for the preparation of benzopyran and benzodihydropyran scaffolds have appeared in the literature, and this review aims to give an overview of the new organocatalyzed syntheses.…”
Section: Introductionmentioning
confidence: 99%
“…The Diels–Alder (DA) reaction is a useful and easy-to-perform method for the synthesis of six-membered rings through the direct formation of C–C bonds between a diene and a dienophile (a substituted alkene); it is called a hetero-Diels–Alder (HDA) reaction when one or more heteroatoms (most often oxygen or nitrogen) are present among the reactants, such as the use of carbonyl compounds or imines as dienophiles [15]. An asymmetric HDA reaction is capable of introducing up to four stereogenic centers in a one-step [4 + 2] cycloaddition or cyclization reaction [68] and it has become hugely popular in preparing vital intermediates for the syntheses of key structural subunits of natural products with biological activities (e.g., carbohydrates, antibiotics, toxins etc.) [910].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Given the importance of this privileged chiral structure, considerable efforts have been devoted to developing versatile methods for their asymmetric synthesis. [3] Over the past decades, various approaches such as asymmetric nucleophilic addition to benzopyrylium ion, [4] asymmetric trapping of orthoquinone methide, [5] and intermolecular cyclization under asymmetric iminium-allenamine catalysis, [6] among others, [7] have been successfully developed to achieve a series of chiral 4H-chromenes. Despite the merits of these approaches, the existing strategies are generally not applicable to the synthesis of 4-alkyl-4Hchromenes.…”
mentioning
confidence: 99%